Corrosion Behavior of Passivated CUSTOM450 and AM350 Stainless Steels for Aeronautical Applications - Samaniego Gámez, Pedro Oliver; Almeraya Calderón, Facundo; Chacón Nava, José G.; Maldonado Bandala, Erick; Nieves Mendoza, Demetrio; Flores de los Ríos, Juan Pablo; Jáquez Muñoz, Jesús Manuel; Delgado, Anabel D.; Gaona Tiburcio, Citlalli (Molecular Diversity Preservation International, 2022)
Custom 450 stainless steel and AM 350 stainless steel are both precipitation hardening stainless steels, which are widely used in a variety of aerospace applications. The former steel exhibits very good corrosion resistance with moderate strength, whereas the latter is used for applications requiring high strength along with corrosion resistance. In this study, the corrosion behavior of CUSTOM 450 and AM 350 stainless steels passivated in (a) citric acid and (b) nitric acid solutions for 50 and 75 min at 49 and 70 °C, and subsequently exposed in 5 wt. % NaCl and 1 wt. % H2SO4 solutions are investigated. Two electrochemical techniques were used: electrochemical noise (EN) and electrochemical impedance spectroscopy (EIS) according to ASTM G199-09 and ASTM G106-13, respectively. The results indicated that passivation in nitric acid made the surface prone to localized corrosion. Statistical and PSD values showed a tendency toward pitting corrosion. On the whole, passivated CUSTOM 450 stainless steel showed the best corrosion behavior in both, NaCl and H2SO4 test solutions.